Struggles for power in the Kingdom of Italy : the Hucpoldings, c. 850-c. 1100 - Manarini, Edoardo (Italy in late antiquity and the early Middle Ages., 2022)
This book presents a detailed study which focuses upon the Hucpoldings, an elite group in Carolingian and post-Carolingian Italy. Though the Hucpoldings have not received extensive treatment in previous Anglophone scholarship, they are a key clan in this period. Manarini's study uses this kinship group to highlight and pinpoint the dramatic geopolitical changes in the kingdom of Italy across three crucial centuries. The research deals with the reconstruction of the political events of every identifiable member of the kinship, as well as the inquiry into their patrimony and their networks of relations and patronage throughout the kingdom of Italy. Finally, it examines the particular elements of the group, from which emerges a clearer picture of the nature of their power, their memory strategies and the shared perceptions and self-awareness among the group members.